Niat Ibu Hamil untuk Tes HIV di UPT (Unit Pelayanan Terpadu) Puskesmas Alun-Alun Kabupaten Gresik - Ernawati, Ernawati; Suryoputro, Antono; Mustofa, Syamsulhuda Budi (Jurnal Promosi Kesehatan Indonesia, 2016)
ABSTRACTThe spreading of HIV infection from mother to child is the main cause of HIV infection towards child below fifteen years old. The examination of HIV towards pregnant mother is a good opportunity to protect the spreading of HIV from mother to baby, wherein all pregnant mothers are suggested to have HIV test. This research aims  to know factors of pregnant mother’s intention to get HIV test at UPT (Integrated Service Unit) of Public Health Center of Gresik Regency Town Square in 2015. Explanatory research which uses survey method with cross sectional approach. The samples of this research is pregnant mothers who carry out antenatal care examination at UPT (Integrated Service Unit) of Public Health Center of Regency Town Square uses purposive sampling technique with the amount of samples as many as 125 peoples. This research uses questionnaire instruments. Its relation analysis uses Chi Square and multivariate analysis by using logistic regression. Of research indicates that pregnant mothers who intend to get HIV test are 54,4%, while those less intend are 45,6%. Variables which are related to pregnant mother’s intention to do HIV test are knowledge about HIV/AIDS, HIV test, perception of severity, self efficacy, and midwife’s role in giving counseling. UPT (Integrated Service Unit) of Public Health Center of Gresik Regency Town Square is aimed to develop VCT socialization in cooperating with private healthcare institution, cadre, and village in giving information about VCT service.Keywords: intention of having HIV test, pregnant mother, Public Health Center